An empirical investigation of the failure of Eastern German products in Western German markets. (18th January 2006) - Hinck, Wolfgang; Cortes, Angelica; James, Karen
More than a decade after the German reunification, products from the Eastern regions of Germany still don't have a market in the West. Although popular sources have blamed several factors for the failure of Eastern German products, no academic literature can be found that empirically investigates why Western consumers do not purchase products from the Neue Lander. The purpose of this paper is to empirically investigate the contribution of selected factors to the phenomenon under consideration. It is established that demand-related reasons, rather than supply-oriented factors appear to explain the phenomenon.